The assassin bug genus Haematoloecha in Taiwan, with notes on species occurring in the neighbouring areas (Hemiptera: Heteroptera: Reduviidae: Ectrichodiinae) - Rédei, Dávid; Tsai, Jing-Fu (Zootaxa, 2012)
The species of the assassin bug genus Haematoloecha Stål, 1874 (Hemiptera: Heteroptera: Reduviidae: Ectrichodiinae)occurring in Taiwan are surveyed. Five species are recognized, two of them, Haematoloecha curta sp. nov. and H. pusillasp. nov. are described as new. Haematoloecha adachii Tachikawa, 1968 and H. nigrorubra Distant, 1919 are recorded forthe first time from Taiwan. Haematoloecha nigrorubra is recognized as having disjunct East Himalayan–Formosan dis-tribution pattern; a new subspecies, H. nigrorubra conspicua ssp. nov. is described for members of the Taiwanese popu-lation. A revised diagnosis of Haematoloecha is provided, species known to occur in Taiwan are keyed. The synonymyof H. nigriventris (Fallou, 1887) with H. nigrorufa (Stål, 1867) is confirmed. The colour variability of H. nigrorufa is dis-cussed. The following taxonomic changes are proposed: Haematoloecha puetzi (Kerzhner & Günther, 2004), comb. nov.(transferred from Parascadra Miller, 1954); H. nigrorubra Distant, 1919 = H. yunnana Hsiao & Ren, 1981, syn. nov.; H.rubescens Distant, 1883 = H. laeta Breddin, 1913, syn. nov. = H. laeta var. ardens Breddin, 1913, syn. nov. Lectotypes are designated for H. nigriventris, H. nigrorubra, H. nigrorufa and H. rubescens.